Sprayed Ag oxygen reduction reaction gas‐diffusion electrodes for the electrocatalytic reduction of CO2 to CO. Issue 2 (1st November 2022) - Wilde, Patrick; Özden, Anil; Winter, Henrik; Quast, Thomas; Weidner, Jonas; Dieckhöfer, Stefan; Junqueira, João R. C.; Metzner, Matthias; Peter, Willi; Leske, Werner; Öhl, Denis; Bobrowski, Tim; et al.
Abstract: Gas‐diffusion electrodes have been successfully employed in electrochemical chlorine production, and they also hold great potential in the field of electrochemical CO2 reduction. Herein, we demonstrate how sprayed Ag‐based gas‐diffusion electrodes, which show outstanding performance for the reduction of oxygen, need to be modified to produce CO from CO2 . A computer‐controlled automated airbrush‐type spraying setup is used to systematically vary the core fabrication parameters of the process and investigate their effect on the electrochemical performance. Focused ion‐beam milling combined with scanning electron microscopy provides deeper insight into the structure of the electrodes and serves in combination with electrochemical data as the measure for the optimisation. Eventually, electrodes can be produced that suppress the evolution of H2 to the extent that an average Faradaic efficiency of 79% for CO can be maintained for at least 10 h at a current density of −100 mA∙cm −2 . Abstract : Sprayed Ag gas diffusion electrodes were optimised for the electrochemical CO2 reduction by the variation of different fabrication parameters. The obtained electrodes show highly improved performance with high CO to H2 ratios even at high current densities. The optimised version shows a continuous activation and a stable electrocatalytic response for at least 10 h.